Generation of an Fsp1 (fibroblast‐specific protein 1)‐Flpo transgenic mouse strain. Issue 5 (19th March 2020) - Cardot‐Ruffino, Victoire; Chauvet, Véronique; Caligaris, Cassandre; Bertrand‐Chapel, Adrien; Chuvin, Nicolas; Pommier, Roxane M.; Valcourt, Ulrich; Vincent, David; Martel, Sylvie; Aires, Sophie; Kaniewski, Bastien; Dubus, Pierre; et al.
Summary: Recombination systems represent a major breakthrough in the field of genetic model engineering. The Flp recombinases (Flp, Flpe, and Flpo) bind and cleave DNA Frt sites. We created a transgenic mouse strain ([Fsp1‐Flpo]) expressing the Flpo recombinase in fibroblasts. This strain was obtained by random insertion inside mouse zygotes after pronuclear injection. Flpo expression was placed under the control of the promoter of Fsp1 (fibroblast‐specific protein 1) gene, whose expression starts after gastrulation at Day 8.5 in cells of mesenchymal origin. We verified the correct expression and function of the Flpo enzyme by several ex vivo and in vivo approaches. The [Fsp1‐Flpo] strain represents a genuine tool to further target the recombination of transgenes with Frt sites specifically in cells of mesenchymal origin or with a fibroblastic phenotype.